A novel approach to mobility management. - Hutchins, Ron
In this paper, we propose a novel approach to computer mobility. Our approach allows mobility to be rapidly deployed, as the networking infrastructure required for deployment is available off the shelf. Furthermore, a mobile node does not require modifications in order to use these mobile services. While our approach provides rapid deployment and supports both IP and non-IP protocols, only a subset of mobile usage scenarios are offered. In other words, our approach does not solve all the problems of mobility. We discuss the characteristics of mobility usage, and we list the scenarios our approach supports. We believe that the mobile usage scenarios supported by this method are some of the more common usage scenarios. We also believe that investigations into this method will provide more insights into network and mobility research.